Attitudes of women towards pregnancy and delivery following assisted reproductive techniques - Łepecka-Klusek, Celina; Pilewska-Kozak, Anna B.; Jakiel, Grzegorz; Bakalczuk, Grzegorz; Jakiel, Grzegorz; Bakalczuk, Grzegorz (Polish Journal of Public Health, 2011)
Introduction. Pregnancy and delivery are very important events in every woman’s life, not only from a physiological, but also from a social point of view. The problems related to pregnancy and delivery among women treated for infertility often grow out of proportion, as these events are preceded by many years of dreams, desires and effort. Aim. The aim of the study was to analyse the attitudes of women towards pregnancy and delivery following assisted reproductive techniques and to investigate how these attitudes were determined. Material and methods. A questionnaire was designed containing 16 questions, the answers to which could be ranked by the 5-point Likert scale. We surveyed 125 primiparous women whose pregnancies had resulted either from artificial insemination by husband (AIH), artificial insemination by donor (AID) or from in vitro fertilisation with embryo transfer (IVF-ET). Results. Positive attitudes towards pregnancy were encountered significantly more frequently than negative ones (p<0.01). The opposite was true regarding the delivery. The parameters used in this study (with the exception of the question of whether the women had continued their professional work or interrupted it) discriminated between the subjects according to their attitudes towards pregnancy and/or delivery. Conclusions. The attitudes towards pregnancy and/or delivery of women who had undergone assisted reproduction procedures were both positive and negative, but also positive towards pregnancy and negative towards delivery or vice versa. The variables that determined these attitudes were age, standard of living, duration of treatment for infertility and the course of pregnancy and/or its resolution.